ความชุก ความรุนแรงและปัจจัยเสี่ยงที่มีความสัมพันธ์กับสภาวะฟันสึกในประชากรอายุ 35 - 74 ปี อำเภอทองแสนขัน จังหวัดอุตรดิตถ์ - กานต์สิรี สุขเกษม (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Nowadays, people are living longer and have more remaining teeth, therefore, there is a high prevalence of tooth wear which is a lifetime of tooth surface loss and is an irreversible process. The purposes of this cross-sectional descriptive study was to determine the prevalence and severity of tooth wear including the risk factors associated with an occurrence of tooth wear in adults ages between 35 to 74 years old in Thongsaenkhan District, Uttaradit province. The data were collected from May to September 2014. An oral examination based on the clinical examination of tooth wear using the Smith and Knight TWI, Basic Erosive Wear Examination (BEWE) and saliva measurement. A face-to-face interview of demographic data and related risk factors was performed. Descriptive statistics and chi-square testing were used to analyze the data. A total of subjects examined were 385 people. Mean age was 54.3±9.9 years old. The prevalence of three types of tooth wear “abrasion”, “erosion” and “attrition” were 99.2, 80.8 and 57.9 percent respectively. The measure of tooth wear severity using the index of Smith and Knight TWI level 2, level 3 and level 4 were 4.4, 63.9, 31.7 percent respectively. The overall average of severity score was 3.3±0.5. The measure of tooth wear severity using the BEWE in level 2 and level 3 were 5.8 and 94.2 percent respectively. Furthermore, there was an association between sex, age and the salivary flow rate and the level of tooth wear severity. This study revealed the high level of prevalence and severity and associated risk factors of tooth wear. There is a high priority to prevent and monitor tooth wear by raising awareness and emphasis the importance of the consequences of tooth wear.